Rethinking subnational government capacity in China - Jaros, K (Taylor and Francis, 2016)
It is clear that some subnational governments are better than others at orchestrating major policy programs, yet important questions remain about how and why subnational government capacity varies from case to case. Scholarship that emphasizes political agency in explaining subnational policy outcomes is not always clear as to where such agency comes from. Meanwhile, research that defines the power of subnational units in terms of their formal administrative authority, fiscal capacity, and political status does not fully explain how these structural endowments translate into effective agency. This article works toward a conception of subnational government capacity better able to integrate these approaches and bridge the agency-structure divide. I call for greater attention to the connective structures that enable subnational governments to take the initiative in policymaking and mobilize resources, stressing provinces’ internal cohesion and upward political ties. To illustrate the need for a broader conception of subnational capacity, and to show the importance of connective power in action, I analyze the contrasting outcomes of regional development strategies in two Chinese provinces.